Causative Organisms and associated antimicrobial resistance in Central Line-Associated Blood Stream Infections from patients admitted in ICU of tertiary health care hospital of Jammu region. - Rajni Bharti; Priyanka Sharma; Harman multani; Shashi S Sharma (Tropical Journal of Pathology and Microbiology, 2024)
Introduction: CLABSI (Central Line Associated Bloodstream Infection) is the presence of bacteremia originating from a central line catheter. CLABSI is a common cause of health care associated infection, and is a major cause of morbidity and mortality. We did this study to study the incidence, bacteriological profile and antimicrobial susceptibility pattern of the isolates in CLABSI in the Intensive Care Unit (ICU) patients.  Material and methods: This prospective study was conducted for one year in Department of Microbiology on patients admitted in ICU for more than 48 hours with Central line catheter. The CLABSI rate was calculated. The formula for CLABSI Rate used was CLABSI incidence rate which was calculated as no. of CLABSI / no. of central line days × 1000.Results: Out of 448 patients 306 have central line. Out of 306 patients 140 develop symptoms related to device associated infections.  Among 140 patients 27 develop central line associated blood stream infection. The CLABSI rate found was 17.76 per 1000 catheter days. Staphylococcus aureus was the most common pathogen isolated among gram positive cocci. Among gram negative bacilli was Acinetobacter sp. Multi drug resistance was seen in the first line of antibiotics used.Conclusion: CLABSI had a significant impact on the overall healthcare costs. Knowledge about risk factors and infection control measures for CLABSI prevention is crucial for best clinical practice.